Trasformasi digital:: Peluang dan tantangan bagi manajemen strategi Bank Syariah - Anjani, Kin Kin Nilam (Maliki Interdisciplinary Journal, 2024)
Digital Transformation is an ongoing process that involves innovation strategies by utilizing advances in digital technology to build capabilities that can replace business models, collaborative approaches, and organizational culture. Digital transformation in sharia banking which brings new challenges and opportunities in operations and services. In the digital era, Islamic banks must utilize technology to increase efficiency and provide safer and more innovative services. The main challenges faced include data security, low financial literacy and human resource readiness. However, digital transformation also opens up big opportunities, such as expanding the range of services, technology-based product innovation, and increasing customer satisfaction. This article aims to find out how digital transformation in sharia banking, whose presence creates challenges and opportunities that can become threats and drivers of the current condition of sharia banking in the future, as well as identifying strategies to deal with these conditions. This article uses a qualitative method with a literature study approach to explore Islamic bank management strategies in facing these changes. The research results show that with the right strategy, Islamic banks can optimize digital transformation opportunities to achieve sustainable and competent growth.